Collateral Survivorship - Keizer, Arlene R. (Radical Teacher, 2019)
"Collateral Survivorship" analyzes my collegial friendship with a renowned fiction writer recently described as a “skilled predator” in an investigation of sexual harassment and abuse at an elite private academy in New England. Written for an audience of other scholars and writers, my essay is neither an indictment nor a defense; it’s an investigation of the forms of socialization that make even women like myself (feminist writers and scholars) vulnerable to such men. In short, "Collateral Survivorship" is focused upon the heterosexual erotics of instruction, not a particular individual.